A rare case of fenoxaprop-P-ethyl poisoning: Presenting as acute myocardial infarction (Indian Journal of Case Reports, 2018)
Fenoxaprop-P-ethyl (FPPE) is a phenoxy herbicide and exerts its herbicidal action by interfering with fatty acid biosynthesis through inhibition of acetyl-CoA-carboxylase in plant chloroplast and thereby hampering fatty acid synthesis. It also inhibits this enzyme in the mammalian liver and has produced reversible hepatic toxicity in laboratory studies. Poisoning with this herbicide is uncommon, and herbicide product appears to be safe in patients with an acute self-poisoning, particularly in comparison with other herbicides and causing few clinical features. Here, we report the case of a 35-year-old male patient presented with FPPE poisoning. He came with an altered sensorium and later on developed acute myocardial infarction. Even after appropriate management, the patient deteriorated and succumbed.